2018
DOI: 10.1177/0961203317723716
|View full text |Cite
|
Sign up to set email alerts
|

Increased adhesion molecule levels in systemic lupus erythematosus: relationships with severity of illness, autoimmunity, metabolic syndrome and cortisol levels

Abstract: Background This study was performed to assess adhesion molecules in systemic lupus erythematosus (SLE). Methods This case-control study examined 126 SLE patients and 48 healthy individuals. Blood levels of six adhesion molecules, cortisol, nuclear autoantibody (ANA) and anti-double stranded DNA (anti-dsDNA) titers were measured, while disease activity was assessed using the SLE Disease Activity Index (SLEDAI) score. Results Platelet endothelial cell adhesion molecule 1 (PECAM-1), vascular cell adhesion molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 48 publications
(57 reference statements)
1
18
0
Order By: Relevance
“…E-Selectin mediates immune cell adhesion, allowing neutrophils to adhere to vascular endothelial cells. E-selectin has been implicated in several cancers [44][45][46] , and as a potential biomarker for SLE and LN [47][48][49] . In this study, while sE-Selectin emerged as the most discriminatory urinary marker within Caucasian LN patients, it was not promising within the African-American cohort.…”
Section: Discussionmentioning
confidence: 99%
“…E-Selectin mediates immune cell adhesion, allowing neutrophils to adhere to vascular endothelial cells. E-selectin has been implicated in several cancers [44][45][46] , and as a potential biomarker for SLE and LN [47][48][49] . In this study, while sE-Selectin emerged as the most discriminatory urinary marker within Caucasian LN patients, it was not promising within the African-American cohort.…”
Section: Discussionmentioning
confidence: 99%
“…According to our study, serum sVCAM-1 and ET-1 levels were significantly higher in SLE patients compared to healthy controls, which was similar to previous studies. 18,22,4151 Moreover, it was indicated that urinary VCAM-1 was elevated in patients with active SLE or lupus nephritis. 5254 sVCAM-1 could be derived from numerous sources other than activated endothelium including bone marrow stromal cells, lymphatic endothelium and activated dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirm and extend the results of previous studies in Turkish, Indian and Brazilian cohorts with adult-onset SLE. [37][38][39] In this study, we speculate that the PAI-1 4G/5G SNP may alter PAI-1 expression level as we observed that the 5G to 4G switch at −675 position was associated with increased PAI-1 serum concentrations among studied subjects and the PAI-1 5G/5G, 5G/4G, and 4G/4G genotypes were associated with low, intermediate, and high PAI-1 serum levels, respectively. Consistent with these findings, previous studies have explained that the deletion of the PAI 4G allele (only 4 guanine bases) has been associated with the inability to bind a repressor protein that decreases binding of the transcriptional activator, resulting in up to 6 times more PAI-1 mRNA expression and increased circulating PAI-1 levels.…”
Section: Discussionmentioning
confidence: 51%